Moderasi Penghindaran Pajak Pajak terhadap CSR (Corporate Social Responsibility) dengan Harga Saham LQ 45 2018-2022 - Febiola Puspita, Grace; Susy Muchtar (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
This study aims to test the hypothesis of moderation of tax avoidance on CSR with LQ share prices, The sample used in this study is the financial statements of LQ-45 companies listed on the IDX for the 2018-2022 period. The independent variable in this study is CSR, tax and the dependent variable is stock price. The research method used is quantitative research. Based on the results of the study showed that tax avoidance carried out using the effective tax rate (ETR) of 7.086 > 2.002 and the significance value of 0.000 was lower at = 0.05. These results show a significant impact on the value of the company's shares. This supports H1 that tax avoidance has a significant effect on company value. Corporate social responsibility is carried out with an index calculation of 5.393 > 2.002 and a significance level of 0.000 and low = 0.05. These results show a significant impact on the value of the company's shares. This supports H2 that corporate social responsibility has a significant influence on corporate value. Profitability with return on equity (ROE) as an adjustment variable of 2.622 < 2.002, the significance level is 0.011, which is as low as = 0.05. These results well suggest that profitability can increase the impact of tax avoidance on a company's stock value. This supports H3 that profitability can moderate the impact of tax avoidance on the value of company shares. Profitability with return on equity (ROE) as an adjustment variable of -1.654.